Atypical intracranial calcifications in a conventional Radiographic exam - Kruger, Marília Sfredo; Klaes, Amália Izaura N.M.; Souza, Ana Claudia de; Vilaverde, Andreia Wallau; Maciel, Antonio Carlos; Tarasconi, Dorvaldo Paulo; Duarte, Juliana Avila; Vedolin, Leonardo Modesti (Clinical and Biomedical Research, 2015)
An 18-year-old male patient of consanguineous parents, delivered at full-term by cesarean section and having no changes in neurodevelopment, presented with skin blisters that evolved to eruptions and scars immediately after birth. In childhood, he developed lesions and diffuse tongue hypertrophy, with cutaneous hyperkeratosis and periods of exacerbation after sun exposure or trauma. In regular outpatient appointments with the medical assistant team, neurological symptoms were not observed. He underwent surgery because of an obstruction of the salivary duct with local abscess. A biopsy of skin lesion was performed and its histological analysis suggested lipoid proteinosis.